The Legacy of Courtly Literature
XII, 234 p. 9 illus.
Keywords: This fascinating volume examines the enduring influence of courtly tradition and courtly love, particularly in contemporary popular culture. The ten chapters explore topics including the impact of the medieval troubadour in modern love songs, the legacy of figures such as Tristan, Iseult, Lancelot, Guinevere, and Merlin in modern film and literature, and more generally, how courtly and chivalric conceptions of love have shaped the Western world’s conception of love, loyalty, honor, and adultery throughout history and to this day. .